2015
DOI: 10.1007/s10098-015-1057-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbon content in the mixture of substrates on methane production

Abstract: A lot of different chemical reactions take place in the biochemical process of biogas formation but the most important of them include the reaction of bonding carbon dioxide with hydrogen and the decomposition of acetic acid. Other factors, such as temperature, pH, etc., only limit the amount of methane or, in extreme cases, they even stop the process of methane formation. The paper presents an analysis of the influence of the amount of available carbon in the substrate and inoculum on biogas production, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The amount of carbon available of the substrate determines the maximum amount of methane and carbon dioxide that can be formed by anaerobic digestion [58]. We also know that carbon is essential for bacterial growth [59].…”
Section: Comparison Of Nitrogen Carbon and C/n Ratiomentioning
confidence: 99%
“…The amount of carbon available of the substrate determines the maximum amount of methane and carbon dioxide that can be formed by anaerobic digestion [58]. We also know that carbon is essential for bacterial growth [59].…”
Section: Comparison Of Nitrogen Carbon and C/n Ratiomentioning
confidence: 99%
“…P-PO 4 3– influences methanogenesis and upstream metabolic pathways, including acidogenesis and acetogenesis ( Wang et al, 2015 ). DTC availability is a likely determinant of maximum CO 2 and CH 4 production ( Mulka et al, 2016 ), while BOD also implies organic carbon availability ( Vigiak et al, 2019 ). Higher DIC concentration in aquatic environments originate from organic carbon remineralization to CO 2 and methanogenesis ( Ogrinc et al, 2002 ), corroborated by the positive correlation observed.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis revealed that OC and TN content was higher at the time of loading of slurry in the AD compared to that of highest biogas production stage (at Day 35). The amount of carbon available of the substrate determines the maximum amount of CH 4 and CO 2 that can be formed by anaerobic digestion [7]. Conversely, C/N ratio remained lowest in this peak stage of CH 4 production.…”
Section: Discussionmentioning
confidence: 99%
“…However, attention must be paid towards undesired emissions of methane (CH 4 ) and nitrous oxide (N 2 O) from manure storage [6]. Moreover, anaerobic digestion of livestock manure improves organic fertilizer quality compared with undigested manure [7], and the load of the pathogenic microorganisms and related antimicrobial resistance is also decreased through the biological process of anaerobic degradation [8]. The rising energy prices and increasing concern of emission of greenhouse gases are the major concern for the people and agro-industries worldwide to consider the wider application of AD technology.…”
Section: Introductionmentioning
confidence: 99%